Comparison between diagnostic instruments for identifying high-functioning children with autism - Yirmiya, Nurit; Sigman, Marian; Freeman, Betty Jo (Journal of autism and developmental disorders, 1994)
Ratings on the Autism Behavior Checklist for 18 children (ages 9-16) with normal intelligence and infantile autism or infantile autism, residual state, revealed that all subjects met the cutoff score for autism or borderline autism on retrospective ratings, but 14 received current ratings below the cutoff. The Autism Diagnostic Interview ruled out the autism diagnosis for three subjects. (Author/JDD)